Strategi Pemasaran Pendidikan dalam Menumbuhkan Minat Calon Peserta Didik di MA Babul Ulum Mariana - Ibrahim Ibrahim; Choirun Niswah; Lefil Egito (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research aims to analyze education marketing strategies in cultivating the interest of prospective students. The study uses a qualitative research method with descriptive characteristics. Informants include school principals, public relations officers, administrative staff, and students, and the information is obtained through interviews, observations, and documentation. The data analysis techniques consist of data reduction, data presentation, and drawing conclusions. Furthermore, data validity is ensured through triangulation to ascertain the reliability of the data in this research. The results of this study reveal that MA Babul Ulum Mariana employs market targeting strategies to identify market segments based on location, with students as the primary target in their educational marketing efforts. When defining market segments, schools typically establish specific criteria that become the primary focus in educational marketing. In terms of competitive positioning strategies, MA Babul Ulum Mariana undoubtedly has its own advantages and uniqueness in educational marketing. This is done to compete with other educational institutions, as each school has its own flagship programs designed to support student potential development for them to achieve success. In the mix of strategies, MA Babul Ulum Mariana combines various elements to support its educational marketing efforts, including flagship programs, a strategically located school, good collaboration with human resources, and affordable pricing